Province Wide Clinical Governance Network for Clinical Audit for Quality Improvement in Endometrial Cancer Management. Issue 1 (1st January 2012) - Mandato, Vincenzo Dario; Formisano, Debora; Pirillo, Debora; Ciarlini, Gino; Cerami, Lillo Bruno; Ventura, Alessandro; Spreafico, Lorenzo; Palmieri, Tamara; La Sala, Giovanni Battista; Abrate, Martino
Abstract : Background: According to the hub-and-spoke model introduced in the Provincial Healthcare System of Reggio Emilia, early endometrial cancer is treated in peripheral low-volume hospitals (spokes) by general gynecologist, whereas more complex cancers are treated by gynecological oncologists at the main hospital (hub). Objective: To guarantee a uniformly high standard of care to all patients with endometrial cancer treated in hub and spoke hospitals of Reggio Emilia Province. Methods: The specialists of the 5 hospitals of Reggio Emilia Province instituted an inter hospital and multidisciplinary oncology group to write common and shared guidelines based on evidence-based medicine through the use of clinical audit. They valued the process indicators before and after guidelines introduction identifying the site of improvement and verifying the standard achievement. Results: Diagnostic hysteroscopy use increased significantly from preguideline period, 53%, to postguideline period, 74%. Magnetic resonance use and accuracy increased significantly from preguideline to postguideline periods: 8.1% to 35.3% and 37.3% to 74.7%, respectively. Laparoscopy use increased from 1.6% (preguideline) to 18.6 (postguideline). Early surgical complications decreased from 16% (preguideline) to 9% (postguideline). Radiotherapy use increased from 14.% (preguideline) to 32.3% (postguideline). Conclusion: It is possible for a provincial oncology group to build an oncology network providing an improvement in the assistance of patients with endometrial cancer through the use of clinical audit. Clinical audit made it possible to obtain the full attendance of specialists of various disciplines involved in the treatment of endometrial cancer to optimize response time schematizing process.